Um estudo histórico da Associação Beneficente de Educação Neurofuncional Milton Melo – ABENMM - MATIAS, Maria da Conceição Rodrigues (2019)
The present work deals with a study of the Charitable Association of Neurofunctional Education Milton Melo, with the intention of provoking reflections on the conditions that allowed its existence. The objectives are to carry out a study about the needs that led to the creation of the Milton Melo Neurofunctional Education Benefit Associa-tion - ABENMM, to investigate the needs and factors that contributed to its creation and under what conditions the Association was founded, we will also investigate the changes that occurred in the pedagogical proposal of the association and what led them to adopt the Method of Development of Human Potential, idealized by Glenn Doman and his team. We use the studies of JANUZZI (2012), MAZZOTA (2001), RODRIGUES (2008), VERAS (1993), and other authors who also discuss the theme. The research used the qualitative method of the bibliographic type with semi-structured interviews, composed of open questions, with two subjects of the research that were of fundamental importance for the establishment of ABENMM in the Munic-ipality of Abaetetuba-PA. The results obtained by the research show that the creation of the Association was due to the need of families of people with disabilities who were looking for a place to treat and improve the neurological conditions of their chil-dren, the creation of ABENMM followed the same line of creation of other institutions, marked by the initiatives of civil society organizations, which structured spaces for the care of people with special needs.